2003
DOI: 10.1023/a:1024153003249
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In various models of cardiac hypertrophy, e.g. treatment of rats with norepinephrine infusion or pressure overload, increased expression of cytokines together with increase in extracellular matrix proteins (ECMP) was reported. In this study the effect of triiodothyronine (T3) on the expression of mRNA for cytokines and ECMP was investigated. Female Sprague-Dawley rats were treated daily with T3 in a dose of 0.2 mg x kg(-1) of body weight s.c. Changes in the left (LV) and right (RV) ventricular function were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…No report can be found regarding the effects of THs on MMPs and TIMPs expression in the non-infarcted area during late stage post-MI LV remodeling. However, Ziegelhoffer-Mihalovicova et al reported that T3-induced cardiac hypertrophy was not accompanied by cardiac fibrosis but an increase in MMP-2 and TIMP-2 expression [40]. Ghose Roy et al found a reduction in collagen I and III in cardiac tissue with an increase in MMP-1 activity and a decrease in TIMP-3 and TIMP-4 expression in T3-induced cardiac hypertrophy [30].…”
Section: Discussionmentioning
confidence: 99%
“…No report can be found regarding the effects of THs on MMPs and TIMPs expression in the non-infarcted area during late stage post-MI LV remodeling. However, Ziegelhoffer-Mihalovicova et al reported that T3-induced cardiac hypertrophy was not accompanied by cardiac fibrosis but an increase in MMP-2 and TIMP-2 expression [40]. Ghose Roy et al found a reduction in collagen I and III in cardiac tissue with an increase in MMP-1 activity and a decrease in TIMP-3 and TIMP-4 expression in T3-induced cardiac hypertrophy [30].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the cardiovascular effects of thyroid hormones have particularly targeted left ventricular improvement. Nonetheless, little is known about the effect of an excess or deficiency of thyroid hormones on the myocardium collagen gene and the responsiveness of interstitial cells to these hormones [89] , [90] , [91] . One study, however, showed that long term hypothyroidism caused overall cardiac muscle stiffness and left ventricle diastolic wall thickness due to increased collagen I/III-based stiffness [92] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that mRNA for collagen type I, the major fibrillar collagen in the heart, is downregulated by TH treatment both in the myocardium and in CF culture [55]. In similar experiments TH-induced hypertrophy is accompanied by an increase of MMP1, MMP2, and TIMP2 without signs of cardiac fibrosis or inflammatory response [56, 57]. T3 can also repress the activation of some transcription factors such as activator protein 1 (AP-1) [58, 59] that are involved in activation of MMPs and collagen gene expression [60].…”
Section: Thyroid Hormone Homeostatic Action On Cardiac Interstitiumentioning
confidence: 88%